Stacking Effect of Carbon/Glass Fiber During Drilling Operation of Laminated Polymer Composite - A.D. Dubey; J. Kumar; P. Kyratsis; R.K. Verma (Archives of Metallurgy and Materials)
Nowadays, fiber stacks are extensively used in the aircraft and structural component manufacturing industries. It is mainly due to their excellent mechanical and physiochemical performances. The different stacking sequences of fiber materials expand the structural properties due to high-strength carbon fiber and low-cost glass fiber. The fragile and anisotropic conduct of Carbon (Cf) and Glass (Gf) laminates generates different types of complex machining issues. This article focuses on the Drilling test of Carbon/glass fiber hybrid composites using different stacking sequences. The effect of varying stacking orders is explored in this study to identify a feasible composite. The control of varying constraints, namely, spindle speed (N), feed rate (f ), and stacking sequence (SS) of carbon (Cf) and glass fiber (Gf) reinforcement, is performed to achieve the optimal parametric condition. The finding reveals that sample A (C4G4) stacking sequence provides an acceptable value for thrust force 59.05 N and delamination 1.0001 for high drilling efficiency. The stacking technique of carbon/glass layers can be endorsed to the manufacturing sector for cost-effective composite development and a defect-free machining environment.